To simplify the expression 4 + 8(3x - 2) - 7x, we need to apply the order of operations and the distributive property. Let's solve it step by step:
1. First, we need to apply the distributive property. So multiply 8 by each term inside the parentheses:
=> 4 + 8 * 3x - 8 * 2 - 7x
2. Simplify the multiplication:
=> 4 + 24x - 16 - 7x
3. Now, group the like terms together:
=> (24x - 7x) + 4 - 16
4. Simplify the terms within parentheses:
=> 17x - 12
5. Finally, combine the remaining terms:
=> 17x - 12
Therefore, the simplified expression is 17x - 12.
Could you solve this? : What is the expression 4+8(3x−2)−7x when simplified? Apply the order of operations and the commutative and distributive properties. Show all your work
1 answer